A Review of Process Tomography Application in Inspection System - Yasmin, Abdul Wahab; Ruzairi, Abdul Rahim; Mohd Hafiz, Fazalul Rahiman; Herlina, Abdul Rahim; Suzanna, Ridzuan Aw; Juliza, Jamaludin; Naizatul Shima, Mohd Fadzil (Penerbit Universiti Teknologi Malaysia, 2014)
The inspection system is crucial to ensure the system is always in a good condition. A technique that can be used for inspection system is process tomography. By promising non-destructive approach; various types of process tomography applied in civil, manufacturing and electrical applications. The purpose of this paper is to review the types of process tomography such as ultrasonic tomography, x-ray tomography, optical tomography, electrical resistance tomography, and electrical impedance tomography that had been applied to the inspection system. Variety techniques of inspection based on those sensors briefly discussed in this paper. The result showed that the process tomography expanded tremendously in the inspection system. Finally, a potential future research on the inspection system in the civil application proposed in this paper.